2012
DOI: 10.3402/fnr.v56i0.18476
|View full text |Cite
|
Sign up to set email alerts
|

Blood selenium levels and contribution of food groups to selenium intake in adolescent girls in Iceland

Abstract: Background/objectivesSignificant changes have been reported in dietary habits and food availability in Iceland that would be expected to compromise selenium intake and status, especially among young people. These include substantial decreases in the consumption of fish and milk, as well as the selenium content of imported wheat. The aim of this study was to assess selenium in the diet and whole blood of adolescent girls, as well as define the most important foods contributing to intake and blood concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…Although these biomarkers of Pb are correlated, urinary Pb does not predict blood Pb (55), possibly explaining why we did not find an association between urinary Pb and testosterone. On the other hand, blood Se is believed to reflect long-term exposure better than serum Se (56), possibly explaining why we did not find an association between serum Se and testosterone if long-term exposure is more important in relation to testosterone. The selection of the appropriate exposure biomarker, whether in blood, urine, or other human tissues or fluids, should be carefully considered when conducting future epidemiology studies of these and other metals in relation to testosterone.…”
Section: Discussionmentioning
confidence: 70%
“…Although these biomarkers of Pb are correlated, urinary Pb does not predict blood Pb (55), possibly explaining why we did not find an association between urinary Pb and testosterone. On the other hand, blood Se is believed to reflect long-term exposure better than serum Se (56), possibly explaining why we did not find an association between serum Se and testosterone if long-term exposure is more important in relation to testosterone. The selection of the appropriate exposure biomarker, whether in blood, urine, or other human tissues or fluids, should be carefully considered when conducting future epidemiology studies of these and other metals in relation to testosterone.…”
Section: Discussionmentioning
confidence: 70%
“…Un total de 11 artículos fueron identificados en la búsqueda, cinco fueron científicos 11,12,13,14,15 de los cuales de eliminaron tres 11,12,13 por no incluir una de las tres variables y seis estudios teóricos 6,7,8,16,17,18 de los cuales se excluyeron dos 6,8 por no contar con los criterios de inclusión de la relación entre el grupo sanguíneo con al menos una de las dos variables (Figura 1.1).…”
Section: Resultados De Búsquedaunclassified
“…Human dietary intervention studies have demonstrated the potential of Se‐enriched wheat and bread products to increase its biomarkers (Hart et al 2011). Se intake (0.04–200 μg/g) in wheat and bread administrated for several weeks (1–9 weeks) was highly bioavailable because it increased both blood Se and GPx levels (Bryszewska et al 2007; Gudmundsdottir et al 2012; Belobrajdic and Bird 2013; Hurst et al 2013). The Se associated with bread has been particularly well retained by various body tissues (Hart et al 2011; Thiry et al 2012).…”
Section: Nutritional and Human Health Implications Of Selenium‐enrichmentioning
confidence: 99%
“…The area of the circles represents the relative yearly per capita consumption of baked goods, and the red circles denote those countries where baked goods are among the five most relevant foods contributing selenium. Information obtained from Hussein and Bruggeman (1999), Klapec et al (2004), Ramiro‐Anaya (2004), Ventura et al (2007), Navarro‐Alarcon and Cabrera‐Vique (2008), Al‐Ahmary et al (2009), Choi et al (2009), Jenny‐Burri et al (2010), Sioen et al (2010), Támas et al (2010), Fairweather‐Tait et al (2011), Al‐Othman et al (2012), Gudmundsdottir et al (2012), Rayman (2012), Sigrist et al (2012), Beladel et al (2013), Souza et al (2013), Jablonska et al (2013), Waegeneers et al (2013), FAO (2013), Euromonitor International (2013), Joy et al (2014), and Navia et al (2014). MEA = Middle East and Africa.…”
mentioning
confidence: 99%